Source Studies of the History of Defense Structures of Samarkand During the Middle Ages - Sattorov Eldor Bobir o‘g‘li (Web of Journals Publishing, 2023)
This is Samarkand city planning in the article indispensable part calculated defense walls and facilities about information gave written sources study done. Also archaeological excavations as a result determined of cities defense to the walls about archaeological findings written in sources given data with compared.
Keywords: medium centuries, Sogdian, defense constructions, writing sources .